Experiences of Breast Cancer Patients with Acute Skin Toxicity Undergoing Radiotherapy - Nia Mitra Agustin; Arina Widya Murni; Emil Huriani (Indonesian Journal of Global Health Research, 2024)
Radiotherapy for breast cancer has been proven to be highly effective, able to significantly reduce the risk of recurrence and lower the risk of death in the long term. However, behind these great benefits, there are side effects that need to be considered, such as skin toxicity, which can have a significant impact on the patient's physical and psychological condition. Therefore, it is necessary to review various literature to determine the various experiences of breast cancer patients with acute skin toxicity who underwent radiotherapy. Objective: To explore and analyze the experiences of breast cancer patients with acute toxicity undergoing radiotherapy through the literature. Method: Search for articles using the keywords acute skin toxicity AND breast cancer AND experience AND radiotherapy. Articles were searched through three online databases, namely sciencedirect (n = 43 articles), pubmed (n = 38 articles), and proquest (n = 32 articles). A total of 113 articles were collected through the data base. Through three screening processes that met the criteria, 4 articles were obtained. Results: This study found an outline of the classification of themes that emerged, namely: physical, functional, psychological impacts, and prevention of skin disorders due to radiotherapy as well as knowledge of breast cancer patients regarding radiotherapy. It is hoped that the results of this research can contribute to improving health care by expanding the scope of services to not only cover physical problems but also non-physical.